Climate change, agriculture, and adaptation in the Republic of Korea to 2050: An integrated assessment - Cenacchi, Nicola; Lim, Youngah; Sulser, Timothy B.; Islam, Shahnila; Mason-D'Croz, Daniel; Robertson, Richard D.; Kim, Chang-Gil; Wiebe, Keith D. (International Food Policy Research Institute, 2016)
As the effects of climate change set in, and population and income growth exert increasing pressure on natural resources, food security is becoming a pressing challenge for countries worldwide. Awareness of these threats is critical to transforming concern into long-term planning, and modeling tools like the one used in the present study are beneficial for strategic support of decision making in the agricultural policy arena. The focus of this investigation is the Republic of Korea, where economic growth has resulted in large shifts in diet in recent decades, in parallel with a decline in both arable land and agricultural production, and a tripling of agricultural imports, compared to the early 2000s. Although these are recognized as traits of a rapidly growing economy, officials and experts in the country recognize that the trends expose the Republic of Korea to climate change shocks and fluctuations in the global food market. This study uses the IMPACT (International Model for Policy Analysis of Agricultural Commodities and Trade) economic model to investigate possible future trends of both domestic food production and dependence on food imports, as well as the effects from adoption of agricultural practices consistent with a climate change adaptation strategy. The goal is to help assess the prospects for sustaining improvements in food security and possibly inform the national debate on agricultural policy. Results show that historical trends of harvested area and imports may continue into the future under climate change. Although crop models suggest negative long-term impacts of climate change on rice yield in the Republic of Korea, the economic model simulations show that intrinsic productivity growth and market effects have the potential to limit the magnitude of losses; rice production and yield are projected to keep growing between 2010 and 2050, with a larger boost when adoption of improved technologies is taken into consideration. At the same time, food production and net exports from the country’s major trading partners are also projected to increase, although diminished by climate change effects. In sum, these results show that kilocalorie availability will keep growing in the Republic of Korea, and although climate change may have some impact by reducing the overall availability, the effect does not appear strong enough to have significant consequences on projected trends of increasing food security.